2020
DOI: 10.7759/cureus.8921
|View full text |Cite
|
Sign up to set email alerts
|

Review of 177Lu-PSMA-617 in Patients With Metastatic Castration-Resistant Prostate Cancer

Abstract: Prostate-specific membrane antigen (PSMA) is a cell membrane glycoprotein that is selectively expressed in prostate cells, with expression levels increasing dramatically in prostatic adenocarcinoma. PSMA-based radioligand therapy (RLT) has emerged as a viable therapeutic modality for the treatment of progressive metastatic prostate cancer. One commonly employed combination involves lutetium-177 conjugated to the ligand PSMA-617 (177 Lu-PSMA-617). In this meta-analysis, we examine therapeutic responses in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…PSMA-targeted radiotherapies are poised to offer an even more impactful alternative, being effective for both PSMA-expressing bone and soft tissue metastases ( 67 ). To date, the most tested PSMA-targeted agent is 177 Lu-PSMA-617, among other agents outlined in Table 1 , with several clinical studies showing significant treatment response, both by imaging and PSA monitoring ( 68 70 ). The largest randomized phase III trial comparing 177 Lu PSMA-617 to standard of care alone in 831 patients with advanced metastatic castration-resistant prostate cancer (mCRPC) (VISION) demonstrated that 177 Lu PSMA-617 significantly improves overall survival (OS, median, 15.3 vs .…”
Section: Therapeutic Role Of Psma In Metastatic Diseasementioning
confidence: 99%
“…PSMA-targeted radiotherapies are poised to offer an even more impactful alternative, being effective for both PSMA-expressing bone and soft tissue metastases ( 67 ). To date, the most tested PSMA-targeted agent is 177 Lu-PSMA-617, among other agents outlined in Table 1 , with several clinical studies showing significant treatment response, both by imaging and PSA monitoring ( 68 70 ). The largest randomized phase III trial comparing 177 Lu PSMA-617 to standard of care alone in 831 patients with advanced metastatic castration-resistant prostate cancer (mCRPC) (VISION) demonstrated that 177 Lu PSMA-617 significantly improves overall survival (OS, median, 15.3 vs .…”
Section: Therapeutic Role Of Psma In Metastatic Diseasementioning
confidence: 99%
“…PSMA is known to be highly expressed on prostate cancer cells at the primary tumor and within visceral and bone metastases [ 123 ]. PSMA-617, a small molecule that binds to PSMA with high affinity, was designed to target PSMA-expressing prostate cancer cells ( Figure 2 B) [ 124 ]. In a recent single-arm, single-center, phase II trial, 177 Lu-PSMA-617 was administered to men with metastatic castration-resistant prostate cancer ( n =30) [ 125 ].…”
Section: Treatment Of Bone Metastasesmentioning
confidence: 99%
“…Randomized controlled trials are running to generate evidence of 177 Lu-PSMA's clinical effectiveness and safety compared to present-day treatments, such as chemotherapy, radiotherapy, and androgen blockade. The innovation also lacks evidence in different settings, such as different patient populations, cotreatment, dosage cycles, and dosage intensities [18]. Hence, the optimal valuing methods of 177 Lu-PSMA's expected benefits still have to be determined for short-and long-term cost-effectiveness analyses.…”
Section: Value Propositionmentioning
confidence: 99%
“…Current literature on 177 Lu-PSMA mainly focuses on its expected clinical efficacy and safety (the first and second NASSS domains) [4,6,8,18]. Based on the NASSS framework, we propose four implementation domains: (1) value proposition, (2) organizational readiness, (3) operational readiness, and (4) environmental management.…”
mentioning
confidence: 99%